Worshiping with the Anaheim Vineyard: the emergence of contemporary worship - Park, Andy (The church at worship, 2017)
"Using narrative, testimonies from leaders and members, and photographs, this book tells the story and explains the remarkable influence of the Vineyard Church of Anaheim on both the early years of the Vineyard movement and the emergence of contemporary worship in the broader church. Not only does this volume present an in-depth look at the congregation's pastor, John Wimber, and the church's first several years, it also tells an inspiring story of revival and renewal for people hungering for deeper knowledge of God. With interviews, sermon excerpts, sidebars, timelines, and a glossary of terms to enhance the text, Worshiping with the Anaheim Vineyard addresses core issues about knowing God intimately for all Christians."--